Cardiac parasympathetic activity during the early hours of acute myocardial infarction. Issue 3 (September 1989) - McAreavey, D; Neilson, J M; Ewing, D J; Russell, D C
Abstract : Cardiac parasympathetic activity was assessed in 21 patients during the first 24 hours of acute myocardial infarction by measuring abrupt beat by beat changes in RR interval, which are expressed as "RR counts". Eleven patients had inferior wall infarction and 10 had anterior wall myocardial infarction. The whole recording period was analysed in 11 patients (five inferior and six anterior), and intermittent hourly periods were analysed in all 21 subjects. Mean RR counts were significantly lower in patients with anterior than inferior infarction, and below the normal range. Although mean heart rates were faster in the group with anterior infarction, there was a dissociation between RR counts and mean heart rate that was consistent with RR interval variability being an independent measure of parasympathetic activity. This study indicates that cardiac parasympathetic activity during acute myocardial infarction can be simply and reliably assessed from continuous electrocardiographic recordings, and it showed significantly lower cardiac parasympathetic activity in patients with anterior infarction.